2019
DOI: 10.1039/c8cp07705c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of confinement in multimolecular inclusion compounds of melamine and cyanuric acid

Abstract: Cyanuric acid is shown to be the best supramolecular building block to obtain cage-like clusters. Its triazine ring is also superior to the melamine one for capturing anions as well as cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The study of these cavity effects is challenging and has been principally proposed on the grounds of computational studies. 115 The nanoreactors (nanosized reaction vessels) enable these cavity effects to be studied experimentally and they can be used as a sustainable future tool for synthesis by harnessing technique used by enzymes in nature. The reactions studied within these nanovessels are highly accelerated and regio-and enantio-selective.…”
Section: Msccs As Reaction Vesselsmentioning
confidence: 99%
“…The study of these cavity effects is challenging and has been principally proposed on the grounds of computational studies. 115 The nanoreactors (nanosized reaction vessels) enable these cavity effects to be studied experimentally and they can be used as a sustainable future tool for synthesis by harnessing technique used by enzymes in nature. The reactions studied within these nanovessels are highly accelerated and regio-and enantio-selective.…”
Section: Msccs As Reaction Vesselsmentioning
confidence: 99%
“…The M-CA system is a classical example of molecular self-assembly governed by strong hydrogen bonding and soft π–π interactions (aromatic stacking). The results of the density functional theory (DFT) studies , confirm that high stability of the macroscale M-CA crystals is a result of the large number of intermolecular hydrogen bonds formed between M and CA (Figure ), among which N–H···N bonds are almost two times stronger than N–H···O . The most energetically favorable structures are rosette-like patterns, linear tapes, and their combinations .…”
Section: Introductionmentioning
confidence: 76%
“…This CA based cylindrophane was able to selectively trap a fluoride ion via anion‐π interactions and hydrogen bonds. In a previous work, we have computationally demonstrated that CA is able to form a hydrogen‐bonded quartet with a cage like structure [14] . We also have shown that this complex can also coordinate a sodium chloride ion pair within its cavity through C=O⋅⋅⋅Na + and π⋅⋅⋅Cl − interactions.…”
Section: Introductionmentioning
confidence: 78%
“…Good and effective anion receptors are usually macrocycles or systems with a certain cavity [1,4] . It is known from a previous work [14] that CA is able to form a hydrogen‐bonded quartet with a cage‐like structure. Within its cavity, the four CA molecules can hold a NaCl ion pair (see Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation